Celebrating Canada. - Blake, Raymond B. (Raymond Benjamin); Hayday, Matthew, 1977- (University of Toronto Press, 2016)
"Holidays are a key to helping us understand the transformation of national, regional, community and ethnic identities. In Celebrating Canada, Matthew Hayday and Raymond Blake situate Canada in an international context as they examine the history and evolution of our national and provincial holidays and annual celebrations. The contributors to this volume examine such holidays as Dominion Day, Victoria Day, Quebec's Fête Nationale and Canadian Thanksgiving, among many others. They also examine how Canadians celebrate the national days of other countries (like the Fourth of July) and how Dominion Day was observed in the United Kingdom. Drawing heavily on primary source research, and theories of nationalism, identities and invented traditions, the essays in this collection deepen our understanding of how these holidays have influenced the evolution of Canadian identities."--